Incidence and Clinical Implications of Anatomical Variations in the Pancreas and Its Ductal System: A Systematic Review and Meta-Analysis - Mathias Orellana-Donoso; Daniel Milos-Brandenberg; Andoni Benavente-Urtubia; Javier Guerra-Loyola; Alejandro Bruna-Mejias; Pablo Nova-Baeza; Álvaro Becerra-Farfán; Walter Sepulveda-Loyola; Ricardo Miguel Luque-Bernal; Juan José Valenzuela-Fuenzalida (Life, 2023)
Objective: This systematic review analyzes the anatomical variants in the pancreas and its ductal system to report on their association with pancreatic pathologies. Methods: We conducted a search of the MEDLINE, Scopus, Web of Science, Google Scholar, CINAHL, and LILACS databases from their inception to July 2023. The methodological quality was assessed with the Anatomical Quality Assessment (AQUA) tool. Finally, the pooled prevalence was estimated using a random effects model. Results: 55 studies were found that met the eligibility criteria. The overall prevalence of pancreas divisum (PD) was 18% (95% CI = 15–21%). The prevalence of PD associated with pancreatitis was 30% (95% CI = 1–61%). Conclusions: An anatomical variant of the pancreas such as PD may be the cause of bile duct obstruction, resulting in various clinical complications, such as pancreatitis. Hence, knowing this variant is extremely important for surgeons, especially for those who treat the gastroduodenal region.